Comparative pathology of experimental pulmonary tuberculosis in animal models - Hunter, Laura; Ruedas-Torres, Inés; Agulló-Ros, Irene; Rayner, Emma; Salguero, Francisco J. (Frontiers in Veterinary Science, 2023)
Research in human tuberculosis (TB) is limited by the availability of human tissues from patients, that usually which is often are altered by therapy and treatment. Thus, the use of animal models within the experimental TB field is a key tool into increasinge our understanding of the pathogenesis, disease progression and preclinical evaluation of new therapies and vaccines. The granuloma is the hallmark lesion of pulmonary tuberculosis, regardless of the species or animal model used. Although animal models may not fully replicate all the histopathological characteristics observed in natural, human TB disease, each oneanimal model brings its own attributes which enable researchers to answer specific questions regarding TB immunopathogenesis. This review delves into the pulmonary pathology induced by Mycobacterium tuberculosis complex (MTBC) bacteria in different animal models (nonhuman primates, rodents, guinea pigs, non-human primates, rabbits, zebrafish, cattle, and goats, and others) and compares how they relate to the pulmonary disease described in humans.Although the described models have demonstrated some histopathological features in common with human pulmonary TB, these data should be considered carefully in the context of this disease. More Further research is necessary to establish the best and most appropriate model for the study of TB, and to carry out a standard characterisation and score of pulmonary lesions.